Improving the method of determin-ing the mass fraction of magnesium carbonate and the study of the chemical composition of carbonate rocks for the effective conduct of the technological process of sugar production - Kos, Tatiana; Kuznietsova, Inha; Sheiko, Tamila; Khomichak, Liubomyr; Bal-Prylypko, Larysa; Vasyliv, Volodymyr; Gudzenko, Maxim; Nikolaenko, Mykola; Bondar, Nikolai; Haidai, Irina (My University, 2021)
The article considers an improved method for determining the content of magnesium carbonate in the carbonate rock. An adjusted method for determining the content of magnesium carbonate was included in the complete establishment of chemical analysis of limestone, which includes the determination of moisture, impurities insoluble in hydrochloric acid, the amount of one and a half oxides of aluminum and iron, calcium carbonate and magnesium carbonate (advanced method), calcium sulfate, alkali metal oxides of potassium and sodium. The obtained experimental data were entered into a single table and summed up the material balance of all components of the carbonate rock. As a result, it was found that this technique includes the following criteria: it is the most accurate, most accessible, and cheap. The use of adjusted methods for determining the content of calcium and magnesium carbonate in limestone will make it possible to establish the objective chemical composition of the carbonate rock and avoid several technological problems. Namely, the excess of uncontrolled magnesium carbonate contributes to the formation of the liquid phase, which in turn reduces the concentration of chemically active lime and promotes the formation of melts in the lime kiln, deteriorating filtration rates, clogging the evaporating station, and so on. Therefore, having information about the real component composition of limestone, the technologist will be able to adjust the technological process in advance, which will lead to the preservation of natural resources while the quality of finished products will not decrease.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; вапняк; карбонат магнія; карбонатна порода; carbonate rock; limestone